Pengaruh Suhu Terhadap Tegangan Tembus Pada Minyak Nabati - Budianto, Budianto; Moh Kamil Amali, Lanto (Jurnal Etnik: Ekonomi-Teknik, 2023)
The depletion of petroleum reserves causes petroleum to become more expensive. Of course, dependence on petroleum must be reduced. One of the uses of petroleum is transformer oil which plays a role as an insulator, coolant, and gas solvent. The aim of the study was to determine the effect of changes on the breakdown voltage in vegetable oils. This study used homogeneous semi-spherical electrodes and a distance between the electrodes of 2.5 mm with an alternating test voltage (AC) frequency of 50 Hz. The temp stress in vegetable oils was tested at normal temperatures, 600C, 900C and 1200C. VCO oil at different temperatures gets a breakdown voltage of 38 kV. In olive oil, the highest breakdown voltage is at 1200C, which is 28 kV. Whereas in hazelnut oil there was no change in the breakdown voltage at 900C and 1200C, namely 34 kV.